Abnormal and normal compulsions - Muris, Peter; Merckelbach, Harald; Clavan, Michel (Behaviour research and therapy, 1997)
Previous research by Rachman and de Silva (1978, Behaviour Research and Therapy, 16, 233–248) and by Salkovskis and Harrison (1984, Behaviour Research and Therapy, 22, 549–552) has shown that abnormal and normal obsessions are similar in content. The present study examined whether the same is true for abnormal and normal rituals. A sample of normal subjects ( N = 150) were asked about their idiosyncratic rituals. A majority of them (54.7%) indicated that they had such rituals. While these rituals were less frequent, less intense, and less often associated with negative affect than the compulsions of a sample of patients with obsessive-compulsive disorder, differences in terms of content between normal and abnormal rituals were small. Experts often tended to misclassify abnormal compulsions as normal rituals. By and large, the present findings indicate that there is a continuity between abnormal and normal compulsions.